Insight into the preponderant role of the lattice size in Sn-based colusites for promoting a high power factor. Issue 19 (20th April 2022) - Kamińska, Paulina; Bourgès, Cédric; Chetty, Raju; Gutiérrez-Del-Río, Daniel; Śpiewak, Piotr; Święszkowski, Wojciech; Nishimura, Toshiyuki; Mori, Takao
Abstract : We investigated the feasibility of the co-doping effect of zinc and chromium for copper and vanadium substitution, respectively, and reported the first successful Cr incorporation within the bulk Sn-based colusite structure. Abstract : We investigated the feasibility of the co-doping effect of zinc and chromium for copper and vanadium substitution, respectively, and reported the first successful Cr incorporation within the bulk Sn-based colusite structure. We demonstrated that this could be achieved by combining process and lattice engineering to open a small solubility window within this sterically restricted V site. The thermoelectric properties of the colusite Cu25 ZnV2− x Cr x Sn6 S32 ( x = 0–0.5) have been examined on sintered ingots over the temperature range of 300–700 K. As a result, we achieved the highest average power factor ever reported for Sn-based colusites. For the first time, our findings point out a striking insight related to the lattice size effect and its contribution to the Seebeck coefficient of Sn-based colusites. All the experimental results were rationalized by theoretical calculations. Using this unique finding, we finally optimized the compound by hot-pressing treatment and reported a competitive zT value of 0.8 at 700 K for the sample Cu25 ZnV1.75 Cr0.25 Sn6 S32 .